Capital structure, liquidity, and firm size impact on profitability of mining industry in Indonesia - Chandra Setiawan; Nemisia Freitas de Jesus Pereira (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
The aim of this research is specifically for measuring the impact of capital structure, liquidity, and firm size on mining industry profitability in Indonesia, both partially and simultaneously. There are five independent variables within this study that are examined by descriptive statistical analysis, classical assumption test, multiple linear regression, and hypothesis testing. In order to select the observation data, purposive sampling method and panel data were used. Adopting quantitative research, there are 119 observation data from 17 samples within the period of 2013 to 2019. Financial ratios used in this study are Debt-to-equity Ratio, Short-term Debt to Asset ratio, Long-term Debt to Asset ratio, Current Ratio, Firm Size, and Return on Equity. DER, STDA, and LTDA are used as the measurement for capital structure, CR as the proxy of liquidity, and FIRMSIZE. Meanwhile, the proxy of profitability is Return on Equity (ROE) which is the dependent variable in this study. The findings of the study reveal that DER, LTDA, and Firm Size all have a significant impact on ROE. On the other hands, STDA and CR do not have a significant effect toward ROE. The most significant independent variable toward ROE is DER.